Rational antimicrobial chemotherapy: assessment of the level of basic knowledge of general practitioners. Final results of the KANT project - Roman A. Bontsevich; Anna V. Adonina; Anna A. Gavrilova; Yana R. Vovk; Maxim L. Maximov; Vera A. Nevzorova; Irina M. Martynenko; Galina G. Prozorova; Elena N. Bochanova; Olga G. Kompaniets; Valeriya O. Barysheva; Galina G. Ketova; et al. (Belgorod National Research University, 2020)
Introduction: The irrational use of medicines leads to a decrease in the quality of care, an increase in treatment costs and side effects. In the case of antibacterial drugs, in addition to all the above-mentioned consequences, their improper use can lead to an aggravation of the existing and quite challenging problem of our time - the growth of antibiotic resistance among pathogenic microorganisms. The aim of the study: to determine the level of basic knowledge of medical specialists in the field of a rational use of antimicrobial drugs (AMD). Materials and methods: The study was based on an analysis of an anonymous multicenter survey in the framework of the KANT project (the full name of the project is "Physicians' (Students') Knowledge of Antimicrobials Usage"). It was conducted in 2018-2019 in 10 major centers of Russia. Results and iscussion: According to the results of the study, the respondents showed a low level of knowledge of the rational use of antibacterial drugs. The best results are obtained for questions No.1 (time interval for evaluating the effectiveness of the initial antimicrobial therapy (AMT)), No.2 (rationality and period of AMD change with a positive clinical effect), and No.9 (determining the mode of using the proposed drugs), whereas the worst results were obtained for questions No.3 (determining irrational combinations of AMD), No.4 (determining a situation requiring a long course of AMT), and No.7 (choosing auxiliary drugs for bacterial respiratory infections). Conclusion: The results obtained in the study indicate the need for additional educational activities among health professionals.